2009
DOI: 10.1007/s00405-009-1010-z
|View full text |Cite
|
Sign up to set email alerts
|

Lipomas of the oral cavity: clinical and histopathologic study of 41 cases in a Brazilian population

Abstract: This study evaluated the clinical and histopathologic aspects of 41 cases of oral lipomas diagnosed in a Brazilian population. All records from patients diagnosed with oral lipoma between 1970 and 2008 were reviewed. Histological sections were evaluated by light microscopy. There was a predominance of females (2.4:1), with a peak incidence between the sixth and seventh decade. The buccal mucosa was the most aVected site (53.7%), followed by the buccal sulcus (14.6%) and tongue (9.8%). Tumor size ranged from 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
71
0
16

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 77 publications
(95 citation statements)
references
References 37 publications
8
71
0
16
Order By: Relevance
“…The mean duration between the first awareness of symptoms and treatment was reported to be ranged 31.2-75.8 months [4,7,8,13,15], and our study showed 12 months. The mean tumor size was previously reported to be ranged from 0.8 to 2.6 cm, and our study showed 2.0 cm.…”
Section: Discussionsupporting
confidence: 50%
See 4 more Smart Citations
“…The mean duration between the first awareness of symptoms and treatment was reported to be ranged 31.2-75.8 months [4,7,8,13,15], and our study showed 12 months. The mean tumor size was previously reported to be ranged from 0.8 to 2.6 cm, and our study showed 2.0 cm.…”
Section: Discussionsupporting
confidence: 50%
“…Most cases of lipoma occur at 60 years of age or older, and are rare in children [4][5][6][7][8][9][10][11][12][13][14][15]. In our study, the mean age of the patients was 59 years, with only one case being less than 40 years old.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations